2003
DOI: 10.1079/bjn2003892
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumour necrosis factor-α and interleukin 6 production by mononuclear cells following dietary fish-oil supplementation in healthy men and response to antioxidant co-supplementation

Abstract: Increased dietary consumption of the n-3 polyunsaturated fatty acids (PUFA) eicosapentaenoic acid (20 : 5n-3; EPA) and docosahexaenoic acid (22 : 6n-6; DHA) is associated with their incorporation into circulating phospholipid and increased production of lipid peroxide metabolites. The relationship between peripheral blood mononuclear cell (PBMC) function, n-3 PUFA intake and antioxidant co-supplementation is poorly defined. We therefore investigated tumour necrosis factor (TNF)-a and interleukin (IL) 6 product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
4
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(132 citation statements)
references
References 33 publications
4
118
4
6
Order By: Relevance
“…They did not report any data on eicosanoid secretion. Other studies, performed in men, report decreased production of various proinflammatory cytokines (15,16) and some state no effect (26) after -3 LCPUFA supplementation. The study by Blok et al is similar to ours with respect to daily -3 LCPUFA dose and use of endotoxin-stimulated whole blood culture, but it was, however, performed in elderly monks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They did not report any data on eicosanoid secretion. Other studies, performed in men, report decreased production of various proinflammatory cytokines (15,16) and some state no effect (26) after -3 LCPUFA supplementation. The study by Blok et al is similar to ours with respect to daily -3 LCPUFA dose and use of endotoxin-stimulated whole blood culture, but it was, however, performed in elderly monks.…”
Section: Discussionmentioning
confidence: 99%
“…B, The observed decrease in LPS-induced PGE 2 secretion in the -3-supplemented group was more pronounced among nonatopic (4 of 5, 80%) than among atopic (11 of 16, 69%) mothers (ns). formed in men with cell cultures established on peripheral blood mononuclear cells (5,15,16). Previous studies in pregnant women supplemented with -3 LCPUFA were mainly focused on consequences for the child (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…4 g/d. Trebble et al (2003a) have reported a negative but 'U-shaped' dose-response relationship between long-chain n-3 PUFA intake and IL-6 production in an open uncontrolled study, with a maximum inhibition demonstrated at a supplementary intake of 1 . 0 g/d.…”
Section: Effects Of Epa and Dha On Natural Killer Cell Activitymentioning
confidence: 98%
“…73 In contrast, n-3 PUFAs may ameliorate the inflammatory response. 74,75 Supplementation with n-3 PUFAs modified phospholipid fatty acid composition and decreased the production of TNF-a and IL-6 by monocytes 76 when compared with palmitic acid. 77 Diets that are high in alinolenic acid (18:3n-3) tend to reduce inflammation.…”
Section: Subclinical Inflammationmentioning
confidence: 99%